I is an other : the secret life of metaphor and how it shapes the way we see the world - Geary, James, 1962- (Harper Perennial, 2012)
Geary's adept explication of the metaphor's role in defining perceptions analyzes how metaphors are used in advertising, scientific discoveries, economics, and politics, as well as how metaphors play in conceptual comprehension and long-term memory